Effect of ginger to overcome nausea and vomiting in pregnant women: a narrative review - Ferila Adiesti; Sulasmi -; Shelly Rodliah Rosyad; Novia DwiJayanti; Melia Dwi Yitna (Universitas Aisyiyah Yogyakarta, 2021)
Background: Nausea, and vomiting (emesis gravidarum) are symptoms that often occur in 60-80% primigravida and 40-60% multigravida. Nausea and vomiting are symptoms experienced by women during early pregnancy, where this condition usually begins 4-8 weeks of pregnancy and can be more severe by the 9th week. The condition of nausea and vomiting will improve at 14 weeks of gestation and above. The discovery of the effectiveness of ginger in reducing nausea and vomiting in pregnancy is a potential health technology assessment that can be recommended in midwifery practice. However, a comprehensive analysis is needed regarding the use of ginger in reducing complaints of nausea and vomiting in pregnancy. Therefore, this analysis was conducted to determine how the effect and safetyness of ginger in reducing nausea and vomiting in pregnancy.Method: The method used was a narrative review method. The articles were searched using 3 databases (PubMed, siencedirect, and Wiley online library). The inclusion criteria of the article were articles published in 2011-2021, in English and discussing the effect of ginger to reduce nausea and vomiting in pregnant women. The article search flow was described using PRISMA Flowchart. Meanwhile, article quality assessment was carried out using MMAT and CASP. Furthermore, data preparation and reporting of results were carried out.Result: Out of the 10 articles that had been extracted,9 article involved pregnant women as participants. while 1 article only discusses the effectiveness of ginger in reducing nausea vomiting,6 articles had been used using randomized controlled trials and 4 articles were systematic reviews. Based on the quality of the articles, 9 articles obtained grade A and 1 article obtained grade B. furthermore, three themes were obtained, namely effectiveness, safety, other therapies, and 5 related sub-themes of effective, ineffective, safety, pharmacological therapy, and non-pharmacological therapy.Conclusion: The findings of this narrative review found that ginger is effective and safe in reducing nausea and vomiting in pregnancy.